PARTISIPASI MASYARAKAT DALAM PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM POS PELAYANANTEKNOLOGI TEPAT GUNA (POSYANTEK) DI KECAMATAN GROGOL PETAMBURAN JAKARTA BARAT - Riza Fauziyah; Muhtadi Muhtadi (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
This study aims to determine the processes and supporting factors inhibiting community participation in the appropriate technology service post program (posyantek). With the formulation of the problem (1) What is the process of community participation in the use of the posyantek program in Grogol Petamburan District? (2) What are the supporting factors and obstacles to community participation in the posyantek program.This research methodology uses qualitative methods and descriptive research types. By using primary and secondary data sources, namely using data obtained from interviews, observations and documentation, as well as data obtained from notes, books, bulletins, written documents related to this research. Through the Posyantek program, it is a community empowerment program to increase knowledge of appropriate technology, provide productive activities and economic change to the beneficiaries as well as the surrounding community as well as assistance to the beneficiaries to become independent in their businesses.The process of empowering the Posyantek Program carried out by the Posyantek Grogol Petamburan sub-district in several villages went through several stages. What dominates in the participation ladder is the 7 partnership ladders on the fourth rung which means providing more real and meaningful participation opportunities for community involvement in local government